Periorbital dermatitis as a side effect of topical dorzolamide. Issue 4 (1st April 2002) - Delaney, Y M; Salmon, J F; Mossa, F; Gee, B; Beehne, K; Powell, S
Abstract : Aim: To report periorbital dermatitis as a late side effect of topical dorzolamide hydrochloride (Trusopt), a drug used to reduce intraocular pressure. Methods: A retrospective study of 14 patients who developed periorbital dermatitis while using topical dorzolamide hydrochloride was undertaken. Six patients underwent patch testing for sensitivity to Trusopt, dorzolamide hydrochloride, and the preservative benzalkonium chloride. Results: The periorbital dermatitis occurred after a mean period of 20.4 weeks of commencing dorzolamide hydrochloride therapy. 13 patients had used preserved topical β blocker treatment for a mean period of 34.2 months without complication before the introduction of dorzolamide. In eight (57.1%) the dermatitis resolved completely after discontinuing dorzolamide but in six (42.9%) resolution of the dermatitis did not occur until the concomitant preserved β blocker was stopped and substituted with preservative free drops. Patch testing for sensitivity to Trusopt, dorzolamide hydrochloride, and benzalkonium chloride was negative. Conclusion: These findings suggest that dorzolamide can cause severe periorbital dermatitis. Although the dermatitis may resolve when dorzolamide is discontinued, this does not always occur and in some patients all topical medication containing benzalkonium chloride needs to be stopped.